Crossing the narrow bridge – among the myth, the rite and the circus act - Чаусидис, Никос (Poznańskie Studia Slawistyczne, 2012)
All of the elements present within the contemporary phenomenon known as ‘circus’ can be found in the symbolic traditions of ancient and archaic cultures, most often manifested as mythical pictures, ritual and magical acts, mythical stories and cult objects. In several previous studies we have tried to find the visual, mythical and symbolic ancient models of some classical circus acts, such as the trapeze, juggling and fire-eating. This paper discusses the act of tightrope walking. The introductory part presents basic information regarding this circus act, along with the phrases, elements and skills it consists of. The text continues with a historical review of this circus skill, which reaches as far back as the great civilizations of the Old World. As a mythical paradigm of this act we took the mythical representations from all over the world regarding crossing the mythical bridge conceived in its cosmological dimension – as communication through the cosmic horizons (sky-earth-underworld). This paper reviews several variants of mythical representations of the narrow bridge between ‘this world’ and the ‘underworld’ registered in different parts of the planet and originating from different ages: the log i.e. a tree trunk bridge, a snake bridge, a phallic bridge, blade bridge, and the hair i.e. string bridge.